Halal Brand Image, Price Fairness, and Purchase Intention in Cosmetic Consumption: Evidence from Wardah Lipstick Users - Tina Fadilah; Verni Y. Ismail (Research of Islamic Economics, 2026)
This study investigates factors influencing consumer purchase intention toward Wardah Glasting lipstick by integrating contemporary marketing perspectives with Islamic ethical values. The growing halal cosmetics market has intensified competition, while consumer decisions are shaped by brand credibility, product value, promotional activities, and perceived fairness. This study examines the effects of influencer marketing, brand image, product quality, and price perception on purchase intention. Using a quantitative explanatory research design, data were collected from 126 respondents through purposive sampling and analyzed using Structural Equation Modeling–Partial Least Squares (SEM–PLS). The results indicate that influencer marketing and product quality do not significantly affect purchase intention, whereas brand image and price perception have significant effects. From an Islamic perspective, based on Ibn Taimiyah's principles, consumer decisions should be supported by fair transactions, truthful marketing, and a balance between price and product value. This study contributes to marketing and consumer behavior literature by demonstrating the importance of perceived fairness and ethical considerations in strengthening consumer trust in halal cosmetic products. The findings provide practical implications for cosmetic companies to develop effective marketing strategies aligned with Islamic ethical values.